Anti-reflection eye protection mask and preparation method thereof
By preparing and spin-coating nano hollow microspheres anti-reflective eye protection mask, the wear problem of traditional anti-reflective film is solved, and long-term maintenance of high light transmittance and low reflectivity is achieved, and it is suitable for a variety of optical applications.
Patent Information
- Application Number
- CN202411845590.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The traditional anti-reflective film is prone to wear out when it is frequently used or cleaned, resulting in a degradation of optical performance.
Nanohol microspheres were prepared by polymerization using amphiphilic macromolecular RAFT reagent, combined with spin coating technology to form an anti-reflective eye protection film on the surface of the glass substrate, and regulate the particle size and dosage of the microspheres to improve light transmittance and reduce reflectivity , and the wear resistance of the film is enhanced by ultrasonic and vacuum drying.
It achieves high light transmittance and low reflectivity in the initial state, and maintains excellent optical performance after polishing, and is suitable for a variety of optical devices.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the field of film technology, in particular to an anti-reflection eye protection film and a preparation method thereof. Background Art
[0002] Anti-reflective eye protection plays an important role in modern optical applications, especially in electronic display devices, eyeglass lenses and other optical devices that need to reduce reflection and increase light transmittance. With the advancement of technology and the improvement of people's requirements for visual comfort, the development of anti-reflective films with excellent optical properties and durability has become a research hotspot.
[0003] The main function of anti-reflection film is to reduce the reflection of light on the surface of the medium and improve the transmittance, thereby enhancing visual clarity and brightness. Traditional anti-reflection film is usually achieved by coating one or more layers of materials with a specific refractive index on the surface of the substrate. These materials reduce the intensity of reflected light through the interference effect. However, traditional methods are insufficient in wear resistance and long-term stability, especially in the case of frequent use or cleaning, the film layer is easily worn, resulting in a decrease in optical performance. Summary of the invention
[0004] In view of this, the purpose of the present invention is to provide an anti-reflective eye protection film and a preparation method thereof, so as to solve the problem that the film layer of the traditional anti-reflective film is easily worn under frequent use or cleaning, resulting in a decrease in optical performance.
[0005] Based on the above purpose, the present invention provides a method for preparing an anti-reflective eye protection film, comprising the following steps: (1) Add methacrylic acid, methyl methacrylate, trithiocarbonate, and 4,4'-azobis(4-cyanovaleric acid) to dioxane, raise the temperature to 70-80°C, perform polymerization reaction for 5-7h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent A; (2) Add methacrylic acid, methyl methacrylate, trithiocarbonate, and 4,4'-azobis(4-cyanovaleric acid) to dioxane, raise the temperature to 70-80°C, perform polymerization reaction for 5-7h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent B; (3) adding the amphiphilic macromolecular RAFT agent A to deionized water, adjusting the pH to 7-8 with sodium hydroxide to obtain an aqueous phase, then mixing methyl methacrylate, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, paraffin and azobisisobutyronitrile to obtain an oil phase, mixing the aqueous phase and the oil phase, stirring for 20-40 minutes, then ultrasonicating for 15-25 minutes, then heating to 65-75°C under a nitrogen atmosphere, reacting for 5-7 hours, and finally vacuum drying to obtain nano hollow microspheres A; (4) adding the amphiphilic macromolecular RAFT agent B into deionized water, adjusting the pH to 7-8 with sodium hydroxide to obtain an aqueous phase, then mixing methyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, paraffin and azobisisobutyronitrile to obtain an oil phase, mixing the aqueous phase and the oil phase, stirring for 20-40 minutes, then ultrasonicating for 30-50 minutes, then heating to 65-75°C under a nitrogen atmosphere, reacting for 3-5 hours, and finally vacuum drying to obtain nano hollow microspheres B; (5) The hollow nanospheres A and B are dispersed in deionized water, and the mixture is spin-coated on the surface of a glass substrate. After the spin-coating, the mixture is vacuum dried to obtain an anti-reflective eye protection film.
[0006] Preferably, the amount of dioxane added in step (1) is 2-5 times the total weight of methacrylic acid, methyl methacrylate, trithiocarbonate and 4,4'-azobis(4-cyanovaleric acid).
[0007] Preferably, in step (1), the molar ratio of methacrylic acid, methyl methacrylate, trithiocarbonate and 4,4'-azobis(4-cyanovaleric acid) is 15-20:10-14:0.8-1.2:0.05-0.15.
[0008] Preferably, the amount of dioxane added in step (2) is 2-5 times the total weight of methacrylic acid, methyl methacrylate, trithiocarbonate and 4,4'-azobis(4-cyanovaleric acid).
[0009] Preferably, in step (2), the molar ratio of methacrylic acid, methyl methacrylate, trithiocarbonate and 4,4'-azobis(4-cyanovaleric acid) is 20-28:3-9:0.8-1.2:0.05-0.15.
[0010] Preferably, the power of ultrasound in step (3) is 400-600w.
[0011] Preferably, in step (3), the weight ratio of the amphiphilic macromolecular RAFT agent A, deionized water, methyl methacrylate, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, paraffin and azobisisobutyronitrile is 15-25:50-110:20-28:10-16:4-8:15-25:0.1-0.3.
[0012] Preferably, in step (4), the weight ratio of the amphiphilic macromolecular RAFT agent B, deionized water, methyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, paraffin wax and azobisisobutyronitrile is 3-7:15-25:4-8:2.5-4.5:1-2:2-8:0.02-0.1.
[0013] Preferably, the power of ultrasound in step (4) is 800-1200w.
[0014] Preferably, the amount of deionized water added in step (5) is 15-30 times the total weight of the hollow nanospheres A and the hollow nanospheres B.
[0015] Preferably, in step (5), the weight ratio of the hollow nanospheres A to the hollow nanospheres B is 2:0.5-1.5.
[0016] Furthermore, the present invention also provides an anti-reflection eye protection film, which is obtained by the preparation method of the anti-reflection eye protection film.
[0017] Beneficial effects of the present invention: The anti-reflective eye protection film of the present invention exhibits excellent optical performance and durability. The film has excellent light transmittance and extremely low reflectivity in the initial state, ensuring clear visual effects and comfortable use experience. More importantly, even after polishing, the film still maintains high light transmittance and low reflectivity, indicating that it can maintain excellent optical properties for a long time during actual use. This stability makes it suitable for a variety of application scenarios, such as glasses, display screens and other optical devices.
[0018] The present invention can effectively adjust the transmittance and reflectance of the film by regulating the length of the hydrophilic segment and the hydrophobic segment of the amphiphilic macromolecular RAFT agent. This is because different segment lengths can adjust the particle size of the nano hollow microspheres A and B, so that the microspheres B with small particle size are filled in the stacking gaps of the microspheres A, reducing scattering and refraction, thereby improving the transmittance and reducing the reflectance.
[0019] The dosage of the hollow nanospheres A and B in the present invention also has a significant effect on the optical properties of the film. The appropriate dosage can significantly reduce the average reflectivity, which is crucial for achieving broadband anti-reflection. However, using one of the microspheres alone will lead to a decrease in wear resistance, because the adhesion between the microspheres in the coating formed by a single microsphere is low and it is easy to fall off during the grinding process. Therefore, a reasonable combination and dosage of microspheres are the key to ensuring film performance. DETAILED DESCRIPTION
[0020] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments.
[0021] Embodiment 1:
[0022] (1) Add 12.9 g of methacrylic acid, 10 g of methyl methacrylate, 2.9 g of trithiocarbonate, and 0.14 g of 4,4'-azobis(4-cyanovaleric acid) to 52 g of dioxane, raise the temperature to 70°C, perform polymerization reaction for 5 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent A; (2) 17.3 g of methacrylic acid, 3 g of methyl methacrylate, 2.9 g of trithiocarbonate, and 0.14 g of 4,4'-azobis(4-cyanovaleric acid) were added to 47 g of dioxane, the temperature was raised to 70°C, the polymerization reaction was carried out for 5 h, and the reaction was carried out by rotary evaporation to obtain an amphiphilic macromolecular RAFT agent B; (3) 15 g of amphiphilic macromolecular RAFT agent A was added to 50 g of deionized water, and the pH was adjusted to 7.1 with sodium hydroxide to obtain an aqueous phase. Then, 20 g of methyl methacrylate, 10 g of hydroxyethyl methacrylate, 4 g of ethylene glycol dimethacrylate, 15 g of paraffin and 0.1 g of azobisisobutyronitrile were mixed to obtain an oil phase. The aqueous phase and the oil phase were mixed, stirred for 20 min, and then ultrasonicated at a power of 400 W for 15 min. Then, the temperature was raised to 65 ° C in a nitrogen atmosphere, and the reaction was carried out for 5 h. Finally, the paraffin and unreacted residual monomers were removed by vacuum drying to obtain nano hollow microspheres A. (4) Add 3 g of amphiphilic macromolecular RAFT agent B to 15 g of deionized water, adjust the pH to 7.2 with sodium hydroxide to obtain an aqueous phase, then mix 4 g of methyl methacrylate, 2.5 g of glycidyl methacrylate, 1 g of ethylene glycol dimethacrylate, 2 g of paraffin and 0.02 g of azobisisobutyronitrile to obtain an oil phase, mix the aqueous phase and the oil phase, stir for 20 min, and then ultrasonicate at a power of 800 w for 30 min, then heat to 65 ° C in a nitrogen atmosphere, react for 3 h, and finally remove the paraffin and unreacted residual monomers by vacuum drying to obtain nano hollow microspheres B; (5) Disperse 20 g of nano hollow microspheres A and 5 g of nano hollow microspheres B in 375 g of deionized water, spin-coat the mixture on the surface of a glass substrate, and then vacuum dry the mixture for 6 h to obtain an anti-reflective eye protection film.
[0023] Embodiment 2:
[0024] (1) Add 15.5 g of methacrylic acid, 12 g of methyl methacrylate, 3.6 g of trithiocarbonate, and 0.28 g of 4,4'-azobis(4-cyanovaleric acid) to 100 g of dioxane, heat to 75°C, perform polymerization for 6 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent A; (2) Add 20.7 g of methacrylic acid, 6 g of methyl methacrylate, 3.6 g of trithiocarbonate, and 0.28 g of 4,4'-azobis(4-cyanovaleric acid) to 100 g of dioxane, raise the temperature to 75°C, perform polymerization for 6 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent B; (3) 20 g of amphiphilic macromolecular RAFT agent A was added to 80 g of deionized water, and the pH was adjusted to 7.5 with sodium hydroxide to obtain an aqueous phase. Then, 24 g of methyl methacrylate, 13.1 g of hydroxyethyl methacrylate, 5.9 g of ethylene glycol dimethacrylate, 20 g of paraffin and 0.2 g of azobisisobutyronitrile were mixed to obtain an oil phase. The aqueous phase and the oil phase were mixed, stirred for 30 min, and then ultrasonicated at a power of 500 W for 20 min. Then, the temperature was raised to 70 ° C in a nitrogen atmosphere, and the reaction was carried out for 6 h. Finally, the paraffin and unreacted residual monomers were removed by vacuum drying to obtain nano hollow microspheres A. (4) Add 5 g of amphiphilic macromolecular RAFT agent B to 20 g of deionized water, adjust the pH to 7.5 with sodium hydroxide to obtain an aqueous phase, then mix 6 g of methyl methacrylate, 3.6 g of glycidyl methacrylate, 1.5 g of ethylene glycol dimethacrylate, 5 g of paraffin and 0.05 g of azobisisobutyronitrile to obtain an oil phase, mix the aqueous phase and the oil phase, stir for 30 min, and then ultrasonicate at a power of 1000 w for 40 min, then heat to 70 ° C in a nitrogen atmosphere, react for 4 h, and finally remove the paraffin and unreacted residual monomers by vacuum drying to obtain nano hollow microspheres B; (5) Disperse 20 g of nano hollow microspheres A and 10 g of nano hollow microspheres B in 600 g of deionized water, spin-coat the mixture on the surface of a glass substrate, and then vacuum dry the mixture for 6 h to obtain an anti-reflective eye protection film.
[0025] Embodiment 3:
[0026] (1) 17.2 g of methacrylic acid, 14 g of methyl methacrylate, 4.3 g of trithiocarbonate, and 0.42 g of 4,4'-azobis(4-cyanovaleric acid) were added to 180 g of dioxane, the temperature was raised to 80°C, the polymerization reaction was carried out for 7 h, and the reaction was carried out by rotary evaporation to obtain an amphiphilic macromolecular RAFT agent A; (2) Add 24.1 g of methacrylic acid, 9 g of methyl methacrylate, 4.3 g of trithiocarbonate, and 0.42 g of 4,4'-azobis(4-cyanovaleric acid) to 190 g of dioxane, raise the temperature to 80°C, perform polymerization reaction for 7 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent B; (3) Add 25 g of amphiphilic macromolecular RAFT agent A to 110 g of deionized water, adjust the pH to 7.8 with sodium hydroxide to obtain an aqueous phase, then mix 28 g of methyl methacrylate, 16 g of hydroxyethyl methacrylate, 8 g of ethylene glycol dimethacrylate, 25 g of paraffin and 0.3 g of azobisisobutyronitrile to obtain an oil phase, mix the aqueous phase and the oil phase, stir for 40 min, and then ultrasonicate at a power of 600 w for 30 min, then heat to 75 ° C in a nitrogen atmosphere, react for 7 h, and finally remove the paraffin and unreacted residual monomers by vacuum drying to obtain nano hollow microspheres A; (4) 7 g of amphiphilic macromolecular RAFT agent B was added to 25 g of deionized water, and the pH was adjusted to 8.0 with sodium hydroxide to obtain an aqueous phase. Then, 8 g of methyl methacrylate, 4.5 g of glycidyl methacrylate, 2 g of ethylene glycol dimethacrylate, 8 g of paraffin and 0.1 g of azobisisobutyronitrile were mixed to obtain an oil phase. The aqueous phase and the oil phase were mixed, stirred for 40 min, and then ultrasonicated at a power of 1200 w for 50 min. Then, the temperature was raised to 75 ° C in a nitrogen atmosphere, and the reaction was carried out for 5 h. Finally, the paraffin and unreacted residual monomers were removed by vacuum drying to obtain nano hollow microspheres B. (5) Disperse 20 g of nano hollow microspheres A and 15 g of nano hollow microspheres B in 1050 g of deionized water, spin-coat the mixture on the surface of a glass substrate, and then vacuum dry the mixture for 6 h to obtain an anti-reflective eye protection film.
[0027] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that the amphiphilic macromolecular RAFT agent A in step (3) is replaced by an amphiphilic macromolecular RAFT agent B; The specific steps are as follows: (1) Add 20.7 g of methacrylic acid, 6 g of methyl methacrylate, 3.6 g of trithiocarbonate, and 0.28 g of 4,4'-azobis(4-cyanovaleric acid) to 100 g of dioxane, raise the temperature to 75°C, perform polymerization for 6 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent B; (2) 20 g of amphiphilic macromolecular RAFT agent B was added to 80 g of deionized water, and the pH was adjusted to 7.5 with sodium hydroxide to obtain an aqueous phase. Then, 24 g of methyl methacrylate, 13.1 g of hydroxyethyl methacrylate, 5.9 g of ethylene glycol dimethacrylate, 20 g of paraffin and 0.2 g of azobisisobutyronitrile were mixed to obtain an oil phase. The aqueous phase and the oil phase were mixed, stirred for 30 min, and then ultrasonicated at a power of 500 W for 20 min. Then, the temperature was raised to 70 ° C in a nitrogen atmosphere, and the reaction was carried out for 6 h. Finally, the paraffin and unreacted residual monomers were removed by vacuum drying to obtain nano hollow microspheres A. (3) Add 5 g of amphiphilic macromolecular RAFT agent B to 20 g of deionized water, adjust the pH to 7.5 with sodium hydroxide to obtain an aqueous phase, then mix 6 g of methyl methacrylate, 3.6 g of glycidyl methacrylate, 1.5 g of ethylene glycol dimethacrylate, 5 g of paraffin and 0.05 g of azobisisobutyronitrile to obtain an oil phase, mix the aqueous phase and the oil phase, stir for 30 min, and then ultrasonicate at a power of 1000 w for 40 min, then heat to 70 ° C in a nitrogen atmosphere, react for 4 h, and finally remove the paraffin and unreacted residual monomers by vacuum drying to obtain nano hollow microspheres B; (4) Disperse 20 g of nano hollow microspheres A and 10 g of nano hollow microspheres B in 600 g of deionized water, spin-coat the mixture on the surface of a glass substrate, and then vacuum dry the mixture for 6 h to obtain an eye protection mask.
[0028] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that the amphiphilic macromolecular RAFT agent B in step (4) is replaced by an amphiphilic macromolecular RAFT agent A; The specific steps are as follows: (1) Add 15.5 g of methacrylic acid, 12 g of methyl methacrylate, 3.6 g of trithiocarbonate, and 0.28 g of 4,4'-azobis(4-cyanovaleric acid) to 100 g of dioxane, heat to 75°C, perform polymerization for 6 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent A; (2) 20 g of amphiphilic macromolecular RAFT agent A was added to 80 g of deionized water, and the pH was adjusted to 7.5 with sodium hydroxide to obtain an aqueous phase. Then, 24 g of methyl methacrylate, 13.1 g of hydroxyethyl methacrylate, 5.9 g of ethylene glycol dimethacrylate, 20 g of paraffin and 0.2 g of azobisisobutyronitrile were mixed to obtain an oil phase. The aqueous phase and the oil phase were mixed, stirred for 30 min, and then ultrasonicated at a power of 500 W for 20 min. Then, the temperature was raised to 70 ° C in a nitrogen atmosphere, and the reaction was carried out for 6 h. Finally, the paraffin and unreacted residual monomers were removed by vacuum drying to obtain nano hollow microspheres A. (3) Add 5 g of amphiphilic macromolecular RAFT agent A to 20 g of deionized water, adjust the pH to 7.5 with sodium hydroxide to obtain an aqueous phase, then mix 6 g of methyl methacrylate, 3.6 g of glycidyl methacrylate, 1.5 g of ethylene glycol dimethacrylate, 5 g of paraffin and 0.05 g of azobisisobutyronitrile to obtain an oil phase, mix the aqueous phase and the oil phase, stir for 30 min, and then ultrasonicate at a power of 1000 w for 40 min, then heat to 70 ° C in a nitrogen atmosphere, react for 4 h, and finally remove the paraffin and unreacted residual monomers by vacuum drying to obtain nano hollow microspheres B; (4) Disperse 20 g of nano hollow microspheres A and 10 g of nano hollow microspheres B in 600 g of deionized water, spin-coat the mixture on the surface of a glass substrate, and then vacuum dry the mixture for 6 h to obtain an eye protection mask.
[0029] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that: in step (5), the amount of nano hollow microsphere A is 10 g, and the amount of nano hollow microsphere B is 20 g; The specific steps are as follows: (1) Add 15.5 g of methacrylic acid, 12 g of methyl methacrylate, 3.6 g of trithiocarbonate, and 0.28 g of 4,4'-azobis(4-cyanovaleric acid) to 100 g of dioxane, heat to 75°C, perform polymerization for 6 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent A; (2) Add 20.7 g of methacrylic acid, 6 g of methyl methacrylate, 3.6 g of trithiocarbonate, and 0.28 g of 4,4'-azobis(4-cyanovaleric acid) to 100 g of dioxane, raise the temperature to 75°C, perform polymerization for 6 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent B; (3) 20 g of amphiphilic macromolecular RAFT agent A was added to 80 g of deionized water, and the pH was adjusted to 7.5 with sodium hydroxide to obtain an aqueous phase. Then, 24 g of methyl methacrylate, 13.1 g of hydroxyethyl methacrylate, 5.9 g of ethylene glycol dimethacrylate, 20 g of paraffin and 0.2 g of azobisisobutyronitrile were mixed to obtain an oil phase. The aqueous phase and the oil phase were mixed, stirred for 30 min, and then ultrasonicated at a power of 500 W for 20 min. Then, the temperature was raised to 70 ° C in a nitrogen atmosphere, and the reaction was carried out for 6 h. Finally, the paraffin and unreacted residual monomers were removed by vacuum drying to obtain nano hollow microspheres A. (4) Add 5 g of amphiphilic macromolecular RAFT agent B to 20 g of deionized water, adjust the pH to 7.5 with sodium hydroxide to obtain an aqueous phase, then mix 6 g of methyl methacrylate, 3.6 g of glycidyl methacrylate, 1.5 g of ethylene glycol dimethacrylate, 5 g of paraffin and 0.05 g of azobisisobutyronitrile to obtain an oil phase, mix the aqueous phase and the oil phase, stir for 30 min, and then ultrasonicate at a power of 1000 w for 40 min, then heat to 70 ° C in a nitrogen atmosphere, react for 4 h, and finally remove the paraffin and unreacted residual monomers by vacuum drying to obtain nano hollow microspheres B; (5) Disperse 10 g of nano hollow microspheres A and 20 g of nano hollow microspheres B in 600 g of deionized water, spin-coat the mixture on the surface of a glass substrate, and then vacuum dry the mixture for 6 h to obtain an eye mask.
[0030] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that only hollow nanospheres A are added in step (5); The specific steps are as follows: (1) Add 15.5 g of methacrylic acid, 12 g of methyl methacrylate, 3.6 g of trithiocarbonate, and 0.28 g of 4,4'-azobis(4-cyanovaleric acid) to 100 g of dioxane, heat to 75°C, perform polymerization for 6 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent A; (2) 20 g of amphiphilic macromolecular RAFT agent A was added to 80 g of deionized water, and the pH was adjusted to 7.5 with sodium hydroxide to obtain an aqueous phase. Then, 24 g of methyl methacrylate, 13.1 g of hydroxyethyl methacrylate, 5.9 g of ethylene glycol dimethacrylate, 20 g of paraffin and 0.2 g of azobisisobutyronitrile were mixed to obtain an oil phase. The aqueous phase and the oil phase were mixed, stirred for 30 min, and then ultrasonicated at a power of 500 W for 20 min. Then, the temperature was raised to 70 ° C in a nitrogen atmosphere, and the reaction was carried out for 6 h. Finally, the paraffin and unreacted residual monomers were removed by vacuum drying to obtain nano hollow microspheres A. (3) Disperse 30 g of nano hollow microspheres A in 600 g of deionized water, spin-coat the mixture on the surface of a glass substrate, and then vacuum dry the mixture for 6 h to obtain an eye mask.
[0031] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that: in step (5), only hollow nanospheres B are added; The specific steps are as follows: (1) Add 20.7 g of methacrylic acid, 6 g of methyl methacrylate, 3.6 g of trithiocarbonate, and 0.28 g of 4,4'-azobis(4-cyanovaleric acid) to 100 g of dioxane, raise the temperature to 75°C, perform polymerization for 6 h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent B; (2) Add 5 g of amphiphilic macromolecular RAFT agent B to 20 g of deionized water, adjust the pH to 7.5 with sodium hydroxide to obtain an aqueous phase, then mix 6 g of methyl methacrylate, 3.6 g of glycidyl methacrylate, 1.5 g of ethylene glycol dimethacrylate, 5 g of paraffin and 0.05 g of azobisisobutyronitrile to obtain an oil phase, mix the aqueous phase and the oil phase, stir for 30 min, and then ultrasonicate at a power of 1000 w for 40 min, then heat to 70 ° C in a nitrogen atmosphere, react for 4 h, and finally remove the paraffin and unreacted residual monomers by vacuum drying to obtain nano hollow microspheres B; (3) Disperse 30 g of nano hollow microspheres B in 600 g of deionized water, spin-coat the mixture on the surface of a glass substrate, and then vacuum dry the mixture for 6 h to obtain an eye protection mask.
[0032] Performance Testing: Reflectivity: The average reflectivity in the wavelength range of 200-700nm was measured by a spectrophotometer. The results are shown in Table 1. Light transmittance: The maximum light transmittance in the wavelength range of 200-700nm was measured by a spectrophotometer. The results are shown in Table 1. Wear resistance: tested with a reciprocating linear wear tester, load 1kg / cm 2 The friction medium is flannel cloth, the wear rate is 40 cycles / min, the wear time is 5 min, and the average reflectivity and maximum transmittance of the film after polishing in the wavelength range of 200-700 nm are tested. The results are shown in Table 1.
[0033] Table 1 Performance test results
[0034] Data Analysis: From the data of Examples 1-3 in Table 1, it can be seen that the anti-reflective eye protection film prepared by the present invention has excellent light transmittance and extremely low reflectivity. Most importantly, after polishing, it still has high light transmittance and low reflectivity, which shows that the anti-reflective eye protection film not only performs well in the initial state, but also can maintain its excellent optical properties for a long time during use, and is suitable for a variety of practical application scenarios.
[0035] From the data of Example 2 and Comparative Examples 1-2 in Table 1, it can be seen that the length of the hydrophilic segment and the length of the hydrophobic segment in the amphiphilic macromolecular RAFT agent can effectively regulate the transmittance and reflectivity of the anti-reflective eye mask. This is mainly because the length of the hydrophilic segment and the length of the hydrophobic segment can effectively regulate the particle size of the nano hollow microspheres A and the nano hollow microspheres B, so that the small-size nano hollow microspheres B are filled in the stacking gaps of the nano hollow microspheres A, reducing the scattering and refraction caused by the stacking gaps, improving the transmittance, and reducing the reflectivity.
[0036] From the data of Example 2 and Comparative Example 3 in Table 1, it can be seen that the dosage of nano hollow microspheres A and nano hollow microspheres B can adjust the light transmittance of the anti-reflection eye protection film, and the appropriate dosage can significantly reduce the average reflectivity, which is crucial for broadband anti-reflection.
[0037] It can be seen from the data of Example 2 and Comparative Examples 4-5 in Table 1 that the use of nano hollow microspheres A or nano hollow microspheres B alone will cause the wear resistance to decrease. This is mainly because the adhesion between the nano hollow microspheres in the coating formed by using nano hollow microspheres A or nano hollow microspheres B alone is low, and they are easy to fall off during the grinding process, forming an uneven surface or directly exposing the glass substrate.
[0038] Those skilled in the art should understand that the discussion of any of the above embodiments is merely illustrative and is not intended to imply that the scope of the present invention is limited to these examples. Under the concept of the present invention, the technical features in the above embodiments or different embodiments may be combined, the steps may be implemented in any order, and there are many other variations of the different aspects of the present invention as described above, which are not provided in detail for the sake of simplicity.
Claims
1. A method for preparing an anti-reflective eye protection film, characterized in that: The following steps are involved: (1) Add methacrylic acid, methyl methacrylate, trithiocarbonate, and 4,4'-azobis(4-cyanovaleric acid) to dioxane, raise the temperature to 70-80°C, perform polymerization reaction for 5-7h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent A; (2) Add methacrylic acid, methyl methacrylate, trithiocarbonate, and 4,4'-azobis(4-cyanovaleric acid) to dioxane, raise the temperature to 70-80°C, perform polymerization reaction for 5-7h, and perform rotary evaporation to obtain an amphiphilic macromolecular RAFT agent B; (3) adding the amphiphilic macromolecular RAFT agent A to deionized water, adjusting the pH to 7-8 with sodium hydroxide to obtain an aqueous phase, then mixing methyl methacrylate, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, paraffin and azobisisobutyronitrile to obtain an oil phase, mixing the aqueous phase and the oil phase, stirring for 20-40 minutes, then ultrasonicating for 15-25 minutes, then heating to 65-75°C under a nitrogen atmosphere, reacting for 5-7 hours, and finally vacuum drying to obtain nano hollow microspheres A; (4) adding the amphiphilic macromolecular RAFT agent B into deionized water, adjusting the pH to 7-8 with sodium hydroxide to obtain an aqueous phase, then mixing methyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, paraffin and azobisisobutyronitrile to obtain an oil phase, mixing the aqueous phase and the oil phase, stirring for 20-40 minutes, then ultrasonicating for 30-50 minutes, then heating to 65-75°C under a nitrogen atmosphere, reacting for 3-5 hours, and finally vacuum drying to obtain nano hollow microspheres B; (5) dispersing the nano hollow microspheres A and nano hollow microspheres B in deionized water, spin coating them on the surface of a glass substrate, and vacuum drying them after spin coating to obtain an anti-reflective eye protection film; In the step (1), the molar ratio of methacrylic acid, methyl methacrylate, trithiocarbonate and 4,4'-azobis(4-cyanovaleric acid) is 15-20:10-14:0.8-1.2:0.05-0.15; In the step (2), the molar ratio of methacrylic acid, methyl methacrylate, trithiocarbonate and 4,4'-azobis(4-cyanovaleric acid) is 20-28:3-9:0.8-1.2:0.05-0.15; In the step (3), the weight ratio of the amphiphilic macromolecular RAFT agent A, deionized water, methyl methacrylate, hydroxyethyl methacrylate, ethylene glycol dimethacrylate, paraffin wax and azobisisobutyronitrile is 15-25:50-110:20-28:10-16:4-8:15-25:0.1-0.3; In the step (4), the weight ratio of the amphiphilic macromolecular RAFT agent B, deionized water, methyl methacrylate, glycidyl methacrylate, ethylene glycol dimethacrylate, paraffin wax and azobisisobutyronitrile is 3-7:15-25:4-8:2.5-4.5:1-2:2-8:0.02-0.1; In the step (5), the weight ratio of the nano hollow microspheres A to the nano hollow microspheres B is 2:0.5-1.
5.
2. The method for preparing the anti-reflection eye protection film according to claim 1, characterized in that: The amount of dioxane added in step (1) is 2-5 times the total weight of methacrylic acid, methyl methacrylate, trithiocarbonate and 4,4'-azobis(4-cyanovaleric acid).
3. The method for preparing the anti-reflection eye protection film according to claim 1, characterized in that: The amount of dioxane added in step (2) is 2-5 times the total weight of methacrylic acid, methyl methacrylate, trithiocarbonate and 4,4'-azobis(4-cyanovaleric acid).
4. The method for preparing the anti-reflection eye protection film according to claim 1, characterized in that: The power of ultrasound in step (3) is 400-600w.
5. The method for preparing the anti-reflection eye protection film according to claim 1, characterized in that: The power of ultrasound in step (4) is 800-1200w.
6. The method for preparing the anti-reflection eye protection film according to claim 1, characterized in that: The amount of deionized water added in step (5) is 15-30 times the total weight of the hollow nanospheres A and B.
7. An anti-reflective eye protection film, characterized in that: The anti-reflective eye protection film is obtained by the preparation method of any one of claims 1 to 6.
Citation Information
Patent Citations
Ultra-hydrophilic antifogging antireflecting coating and preparation method and application thereof
CN101786801A
Polymer surfactant and core-shell amphiphilic polymer microsphere as well as preparation method thereof
CN101982478A
Preparation method of porous antireflection film formed by nanopolymer hollow particles
CN102030483A
Polymer emulsion and preparation method thereof
CN103497272A
Broadband multi-layer anti-reflection film and preparation method thereof
CN103739206A